2010
DOI: 10.1111/j.1744-7976.2009.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

A Seasonal Inverse Almost Ideal Demand System for North American Fresh Tomatoes

Abstract: "Increased fresh tomato trade has prompted a number of trade disputes between the United States, Canada, and Mexico. One precondition of an antidumping dispute is meeting the "likeness of product" criterion. However, fresh tomato shipments and imports are highly seasonal, suggesting that the degree of substitutability (or product likeness) may depend fundamentally on whether fresh tomato varieties are in- or out-of-season. We develop a seasonally adjusted inverse demand system using Canadian and Mexican monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The above highlights how a modernization and restructuring of the supply chain and a change of entrepreneurial strategies of farmers [82] appear necessary so as to favor a more sustainable economic development of farms [83][84][85]. Commercial reorganization and process innovation, in fact, are the main levers to regain market shares from international competitors that, despite their small-sized farms, are able to meet the growing demand of fresh out-of season tomato [86][87][88]. Indeed, profitability is an indispensable prerequisite for long-term competitiveness of farms in an increasingly globalized and competitive market, representing production units that could thereby provide income and job opportunities for a given rural context [89][90][91].…”
Section: Resultsmentioning
confidence: 99%
“…The above highlights how a modernization and restructuring of the supply chain and a change of entrepreneurial strategies of farmers [82] appear necessary so as to favor a more sustainable economic development of farms [83][84][85]. Commercial reorganization and process innovation, in fact, are the main levers to regain market shares from international competitors that, despite their small-sized farms, are able to meet the growing demand of fresh out-of season tomato [86][87][88]. Indeed, profitability is an indispensable prerequisite for long-term competitiveness of farms in an increasingly globalized and competitive market, representing production units that could thereby provide income and job opportunities for a given rural context [89][90][91].…”
Section: Resultsmentioning
confidence: 99%
“…Our data, however, cannot separate unmeasured quality changes associated with ripeness or the psychic benefit of domestic production . While some literature has indicated that even seemingly homogenous products are differentiated by country of origin (Grant et al., ), that issue is outside the scope of this research.…”
Section: Estimation and Resultsmentioning
confidence: 92%
“…The merit of the demand system is that the estimates can be interpreted as commonly used price flexibilities, and the variables defined in the demand system are the relative changes of prices and quantities, which can be obtained from the available data usually expressed in index numbers. Other inverse demand models such as Eales and Unnevehr (1994), Grant, Lambert, and Foster (2010), and Moschini and Vissa (1992) specified some forms of demand systems under the AIDS framework. Although their demand models are capable of generating price flexibilities, the generated price flexibilities may be unstable inasmuch as the price flexibilities are functions of expenditure shares, which are innate stochastic variables in these models.…”
Section: Empirical Modelingmentioning
confidence: 99%